2019
DOI: 10.3991/ijet.v14i09.10048
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Attitude Toward Self-Regulated Learning of Thailand’s Students in Educational Data Mining Perspective

Abstract: The Self-Regulated Learning (SRL) strategies can be the best. It can be achieved by a sub-goal that will be more important in the younger generation. This paper proposes the process of developing factors (attributes) which are related to the development of learning styles through self-regulated strategies. The objectives of this paper are (1) to study the perception and attitude toward the attributes of students with self-regulated learning of the students in higher education, and (2) to find the level of acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Reference n 2015 [22,23] (n = 2) 2016 [24][25][26][27][28][29][30][31] (n = 8) 2017 [32][33][34][35][36][37] (n = 6) 2018 [38][39][40][41][42][43][44][45][46] (n = 9) 2019 [47][48][49][50][51][52][53][54][55][56] (n = 10) 2020 [57][58][59][60][61] (n = 5) 2021 [62] (n = 1)…”
Section: Year Of Publicationmentioning
confidence: 99%
“…Reference n 2015 [22,23] (n = 2) 2016 [24][25][26][27][28][29][30][31] (n = 8) 2017 [32][33][34][35][36][37] (n = 6) 2018 [38][39][40][41][42][43][44][45][46] (n = 9) 2019 [47][48][49][50][51][52][53][54][55][56] (n = 10) 2020 [57][58][59][60][61] (n = 5) 2021 [62] (n = 1)…”
Section: Year Of Publicationmentioning
confidence: 99%
“…The composition of the self-regulated learning consists of three important phases [13], [27], [29]. The first phase is the forethought phase, which consists of two important processes as follows: (1) task analysis, and (2) self-motivation beliefs.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…Details of the components of the Self-regulated learning are shown in Figure 1. From the theory of self-regulated learning, there is a lot of interest in research [13], [14], [17], [28]. It can therefore be concluded that this self-regulated learning theory is appropriate for this research.…”
Section: Self-regulated Learningmentioning
confidence: 99%
See 2 more Smart Citations